Aggregation and pressure effects of asphaltene and resin molecules at oil–water interfaces: a coarse-grained molecular dynamics and free energy study. Issue 2 (2nd July 2020) - Deetz, Joshua D.; Faller, Roland
ABSTRACT: Coarse-grained molecular dynamics simulations were used to investigate the aggregation of asphaltene and resin molecules in oils and their deposition to oil–water interfaces. Resin, "interfacially-active" asphaltenes, and "bulk-like" asphaltenes are considered as solutes in organic phases consisting of aromatics or saturates. Resins and asphaltenes formed aggregates with a spacing of 0.46 nm between stacked polycyclic sheets. Whether in the aromatic or saturated solvent, resin molecules did not interact with the interface, but its aggregates remained in the bulk. The degree of surface activity of asphaltenes was found to increase with the polarity of their chemical groups, and decrease with the aromatics content of the solvent. Axial stress profiles were measured to calculate the interfacial tension of each system. The tension of interfaces of crude oil with water was found to depend on aromatics content. The free energy of deposition of asphaltenes and resin molecules to the interface was measured using well-tempered metadynamics, in which it was found that "interfacially-active" asphaltenes possess greater stability at the oil-water interface than "bulk-like" asphaltenes, and the organic solvent influences the favorability of deposition.